Data and analysis for the CODATA 2017 special fundamental constants adjustment*This report was prepared by the authors under the auspices of the Committee on Data for Science and Technology CODATA Task Group on Fundamental Constants. The members of the task group are F Cabiati, Istituto Nazionale di Ricerca Metrologica, Italy; J Fischer, Physikalisch-Technische Bundesanstalt, Germany; K Fujii, National Metrology Institute of Japan, Japan; S G Karshenboim, Pulkovo Observatory, Russian Federation and Ludwig-Maximilians-Universität, Germany; H S Margolis, National Phyiscal Laboratory, United Kingdom; E de Mirandés, Bureau international des poids et mesures; P J Mohr, National Institute of Standards and Technology, United States of America; D B Newell, National Institute of Standards and Technology, United States of America; F Nez, Laboratoire Kastler-Brossel, France; K Pachucki, University of Warsaw, Poland; T J Quinn, Bureau international des poids et mesures; B N Taylor, National Institute of Standards and Technology, United States of America; M Wang, Chinese Academy of Sciences, People's Republic of China; B M Wood, National Research Council, Canada; Z Zhang, National Institute of Metrology, People's Republic of China. (24th January 2018) - Mohr, Peter J; Newell, David B; Taylor, Barry N; Tiesinga, Eite
Abstract: The special least-squares adjustment of the values of the fundamental constants, carried out by the Committee on Data for Science and Technology (CODATA) in the summer of 2017, is described in detail. It is based on all relevant data available by 1 July 2017. The purpose of this adjustment is to determine the numerical values of the Planck constant h, elementary charge e, Boltzmann constant k, and Avogadro constant N A for the revised SI expected to be established by the 26th General Conference on Weights and Measures when it convenes on 13–16 November 2018.